2020
DOI: 10.3389/fpsyg.2020.00948
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Perceived Organizational Support on Police Job Burnout: A Moderated Mediation Model

Abstract: Objective: Based on the theory of perceived organizational support (POS), conservation of resource (COR) and job demands-resources (JD-R) model, this study establishes a moderated mediation model to test the role of job satisfaction in mediating the relationship between POS and job burnout, as well as the role of regulatory emotional self-efficacy (RES) in moderating the above mediating process.Methods: A total of 784 police officers were surveyed with the POS Scale, the Job Burnout Questionnaire, the RES Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 88 publications
4
51
1
2
Order By: Relevance
“…The results indicated that the level of perceived organizational support is an antecedent of burnout syndrome experienced at work by employees in the medical sector, and the analysis showed that POS has a significant negative effect on personnel job burnout. The findings are consistent with previous studies such as (Zeng et al, 2020;Özyer et al, 2016;Yaghoubi et al, 2014;Alves et al, 2014;Grama & Băiaș, 2018;Walter & Raybould, 2007;Anomneze et al, 2016). In the same vein, we argue that employees who perceive their organizations as supportive and caring are less likely to experience a high level of burnout in their jobs.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The results indicated that the level of perceived organizational support is an antecedent of burnout syndrome experienced at work by employees in the medical sector, and the analysis showed that POS has a significant negative effect on personnel job burnout. The findings are consistent with previous studies such as (Zeng et al, 2020;Özyer et al, 2016;Yaghoubi et al, 2014;Alves et al, 2014;Grama & Băiaș, 2018;Walter & Raybould, 2007;Anomneze et al, 2016). In the same vein, we argue that employees who perceive their organizations as supportive and caring are less likely to experience a high level of burnout in their jobs.…”
Section: Discussionsupporting
confidence: 93%
“…supported by (Anomneze, Ugwu, Enwereuzor, & Ugwu, 2016) findings that POS significantly predicts exhaustion at work. According to (Zeng, Zhang, Chen, Liu, & Wu, 2020) POS has a significant negative predictive effect on workplace burnout. (Walters & Raybould, 2007) found that the higher the level of POS the lower the levels of exhaustion and cynicism, and their findings suggested that social and environmental factors should be considered when studying burnout in the workplace.…”
Section: Perceived Organizational Support and Job Burnoutmentioning
confidence: 95%
See 3 more Smart Citations